Analysis of Inconsistent Routing Components in Reactive Routing Protocols - Rehman, Habib-ur; Wolf, Lars (Electronic Communications of the EASST, 2009)
In reactive routing protocols, additional routing information is often collectedto reduce the response time and the overhead of the future routing demands.However, these protocols do not have any mechanism to refresh this routing informationand soon it become obsolete. Therefore, routing components based on thisprior-to-demand collected information are not consistent with the reactive natureof the protocol. In this work, we have identified such inconsistent components inAODV routing protocol and have analyzed their effect. Our simulation based analysishas revealed that the presence and use of stale routing information degrades theprotocol performance. However, if the dependency of protocol operations on thisobsolete information is reduced, the protocol performs better in terms of overheadand packet delivery ratio.